Cytology and human papillomavirus testing on cytobrushing samples from patients with head and neck squamous cell carcinoma. Issue 22 (9th July 2014) - Donà, Maria Gabriella; Giuliani, Massimo; Vocaturo, Amina; Spriano, Giuseppe; Pichi, Barbara; Rollo, Francesca; Ronchetti, Livia; Covello, Renato; Pescarmona, Edoardo; Benevolo, Maria
<x xml:space="preserve">Abstract</x> BACKGROUND The increasing incidence of human papillomavirus (HPV)‐related head and neck squamous cell carcinoma (HNSCC) highlights the need for simple and effective tools to evaluate head and neck lesions and their HPV status. The main objective of the current study was to investigate the association between abnormal cytology and HPV infection, assessed on cytobrushing samples, and histologically confirmed HNSCC. Second, the authors attempted to investigate whether HPV status on cytobrushing samples reflected that of the tumoral tissue. METHODS A total of 164 samples from HNSCC, nonmalignant lesions, or healthy mucosae of the oral cavity and oropharynx were collected by cytobrushing in PreservCyt solution and evaluated by liquid‐based cytology and Linear Array HPV genotyping test. All the findings from the cytologic samples were compared with those from the corresponding histologic samples. RESULTS Patients with abnormal cytology had a significantly higher risk of having an HNSCC (odds ratio [OR], 9.18; 95% confidence inteval [95% CI], 3.27‐26.49). The association was stronger for oral cancer (OR, 10.86; 95% CI, 2.51‐51.06) than oropharyngeal cancer (OR, 8.45; 95% CI, 1.62‐49.82). HPV positivity in the oropharyngeal cytobrushing was associated with a nearly 5‐fold higher risk of having abnormal cytology (OR, 4.57; 95% CI, 1.57‐13.57) as well as histologically proven oropharyngeal cancer (OR, 5.09; 95% CI, 1.09‐31.61). Comparing the HPV status on cytologic and corresponding histologic samples from patients with HNSCC, we found that 90.4% of the cases were concordant (kappa, 0.796). CONCLUSIONS Abnormal brushing cytology is strongly associated with a diagnosis of HNSCC, whereas HPV positivity on cytobrushing samples is only associated with oropharyngeal cancer. HPV testing on cytobrushing samples represents a valid option for the assessment of HPV infection in patients with oropharyngeal cancer. Cancer 2014;120:3477–3484. © 2014 American Cancer Society.